2014
DOI: 10.1128/aem.01100-14
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silica-Encapsulated Pseudomonas sp. Strain NCIB 9816-4 in Biodegradation of Novel Hydrocarbon Ring Structures Found in Hydraulic Fracturing Waters

Abstract: The most problematic hydrocarbons in hydraulic fracturing (fracking) wastewaters consist of fused, isolated, bridged, and spiro ring systems, and ring systems have been poorly studied with respect to biodegradation, prompting the testing here of six major ring structural subclasses using a well-characterized bacterium and a silica encapsulation system previously shown to enhance biodegradation. The direct biological oxygenation of spiro ring compounds was demonstrated here. These and other hydrocarbon ring com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…Perullini et al () reported a lower E of 0.065 kPa and did not report σ f . The improvement in the mechanical properties achieved here was mainly due to the higher silica content of the gels developed as compared to the previous studies (Aukema et al, ; Dickson and Ely, ; Eleftheriou et al, ; Perullini et al, ; Reátegui et al, ) as σ f and E are strong functions of the silica density within the gel (Woignier et al, ; Woignier and Phalippou, ). This was achieved while the biodegradation activity could be sustained at high levels.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Perullini et al () reported a lower E of 0.065 kPa and did not report σ f . The improvement in the mechanical properties achieved here was mainly due to the higher silica content of the gels developed as compared to the previous studies (Aukema et al, ; Dickson and Ely, ; Eleftheriou et al, ; Perullini et al, ; Reátegui et al, ) as σ f and E are strong functions of the silica density within the gel (Woignier et al, ; Woignier and Phalippou, ). This was achieved while the biodegradation activity could be sustained at high levels.…”
Section: Resultssupporting
confidence: 52%
“…Nevertheless, silica gel bioencapsulation has been investigated as a method for deploying bacteria to remove hydrocarbons from contaminated water (Branyik et al, 1998;Khongkhaem et al, 2011;Pannier et al, 2010;Rodrigues et al, 2013) as well as for other biotechnology applications (Avnir et al, 2006;Gill and Ballesteros, 2000;Meunier et al, 2010;Nassif and Livage, 2011). Biodegradation of aromatic ring systems (Aukema et al, 2014) and complex hydrocarbon solutions (Strong et al, 2013) using silica encapsulation have also been previously studied by our group. While those studies focused on the variety of chemicals degraded by the organisms, they have not delved into the engineering challenges associated with: (i) cytocompatibility of the gel and the encapsulation process; (ii) structural integrity of the silica gel; and (iii) long term, sustained biodegradation activity of the encapsulated cells.…”
Section: Introductionmentioning
confidence: 99%
“…After incubations of 1, 3, and 24 hours, reactions were quenched with an equal volume of ethyl acetate. The organic phase was extracted and 5 μL was analyzed by gas chromatography, splitting the sample between the flame ionization detector and the mass spectrometer as previously described [25]. Elution program conditions consisted of 250°C inlet temperature, 100°C start temperature, 10°C/min ramp rate, 320°C final temperature, and a 5 min hold time (total time of 27 min).…”
Section: Methodsmentioning
confidence: 99%
“…Bioremediation of PAHs is shown to be feasible using Pseudomonas sp. NCIB 981613, but the process requires continuous oxygenation via mechanical aeration. Aeration can account for more than 50% of the overall energy consumption in a typical bioremediation processes14, making bioremediation economically less feasible.…”
mentioning
confidence: 99%